Serum YKL-40 as a Potential Biomarker for Sepsis in Term Neonates-A Pilot Study - Evangelia Steletou; Dimitra Metallinou; Alexandra Margeli; Theodoros Giannouchos; Athanasios Michos; Christina Kanaka-Gantenbein; Ioannis Papassotiriou; Tania Siahanidou (MDPI AG, 2023)
Although YKL-40 is a promising diagnostic biomarker of sepsis in adults, its value in neonatal sepsis is not known. The study objectives included assessing the levels and diagnostic value of serum YKL-40 in term neonates with sepsis and comparing YKL-40 with other commonly used inflammatory biomarkers. In this pilot case-control study, 45 term neonates (30 septic and 15 non-septic, as controls), 4 to 28 days old, were prospectively studied. The International Pediatric Sepsis Consensus Conference criteria were applied to diagnose sepsis. During the acute phase (admission) and remission of sepsis, blood samples were collected from cases (while from controls they were only collected once) for routine laboratory tests, cultures, and the measurement of serum YKL-40 levels via Elisa. In the acute phase of sepsis, YKL-40 levels were significantly elevated in comparison with remission (p = 0.004) and controls (p = 0.003). YKL-40 levels did not differ significantly between patients in remission and controls (p = 0.431). Upon admission, YKL-40 levels correlated positively with white blood count, absolute neutrophil count, and CRP levels. Via ROC analysis, it was shown that YKL-40 levels upon admission were a significant indicator of sepsis (AUC = 0.771; 95% CI 0.632-0.911; p = 0.003). Serum YKL-40 might be considered as an adjuvant biomarker of sepsis in term neonates.